(untitled) (Journal of Governance and Development (JGD), 2022)
In 1952, under the administration of Plaek Phibunsongkhram, the Social Security concept was introduced in Thailand. This led to the first enactment of Social Security Act B.E. 2533 (1990) and Social Security Act (No.3), B.E.2542 (1999). As the Thai society at present, is becoming increasingly interacting with the senior community, but hardly any focus has been placed on assisting and understanding their needs. The elderly has Social Security as a guarantee that they won’t be abandoned when they get old. Therefore, social security is a measure that is crucial and essential for employees who apply for old age insurance. Furthermore, the Social Security Office has prescribed the old age compensation benefit as part of a program to improve quality of life or as a guarantee of employment security while retiring in order to produce long-term benefits for the insurer. This article concerned and discussed on the needs of the insurer who applied old age social security benefit: ensuring rights, dignity as well as income security in later life by using the Hierarchy of Need theory of Abraham Maslow and Alderfer’s ERG Theory of Clayton Alderfer.